Elementary mathematics from an advanced standpoint: Arithmetic algebra, analysis - Klein, FelixKLEIN Felix; Hedrick, E. R.; Noble, C. A. (New York Dover Publications, 1924)
Makes the reader feel the inspiration that comes from listening to a great mathematician." $1 (BBulletin, American Mathematical SocietyA distinguished mathematician and educator enlivens abstract discussions of arithmetic, algebra, and analysis by means of graphical and geometrically perceptive methods. His three-part treatment begins with topics associated with arithmetic, including calculating with natural numbers, the first extension of the notion of number, special properties of integers, and complex numbers. s
Keywords: Mathematics; Applied mathematics